Serum-Based Proteomics Reveals Lipid Metabolic and Immunoregulatory Dysregulation in Cervical Artery Dissection With Stroke - Yang, Yongtao; Peng, Jing; Wang, Suxia; Huang, Jialu; Ran, Hong; Chen, Kangning; Zhou, Zhenhua (Frontiers in Neurology, 2020)
Cervical artery dissection (CAD) is an important causal factor for stroke in young and middle-aged individuals and presents a great burden to the individual stroke victim. However, the pathophysiological mechanisms underlying CAD remain unknown. Here, an isobaric tagging for relative and absolute quantitation (iTRAQ)-based quantitative proteomic approach was performed, to identify differentially expressed proteins in serum samples obtained from spontaneous CAD and non-CAD ischemic stroke subjects. Differential protein expression was analyzed for Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway over-representation, and six differential proteins were selected for enzyme-linked immunosorbent assay (ELISA) validation. Through KEGG analysis, the significantly differentiated proteins were primarily involved in immunoregulation, blood coagulation, and lipid metabolism. For the first time, differential expressions of apolipoprotein B (APOB), apolipoprotein C-I (APOC-I), lipopolysaccharide-binding protein (LBP), vascular cell adhesion molecule 1(VCAM1), fibulin-1 (FBLN1), and ficolin-2 (FCN2) were confirmed as being significantly upregulated in CAD as compared to non-CAD ischemic stroke subjects. In conclusion, proteomic analysis reveals that early perturbation of immunoregulation and lipid metabolism may be involved in the pathophysiology of CAD. Specifically, the panel of six proteins identified are promising as serum-based biomarkers for the detection of increased CAD risk in stroke subjects.